2020
DOI: 10.1039/d0ce00770f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron-withdrawing moieties on mechanochromism of phenothiazine derivatives

Abstract: Two phenothiazine derivatives with electron-withdrawing cyano and ester groups emitted longer wavelength fluorescence and exhibited different mechanochromic behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…It has been reported that the cyanostyrene derivatives could exhibit MFC properties and the planar architecture of pyrenebased conjugated compounds is favorable for MFC. 38,[40][41][42] To test their possible MFC properties, the solid-state fluorescence changes of PYTPA and PYPHTPA were examined before and after grinding. The emission peak of PYTPA exhibits a red shift of 0.199 eV (Δλ PYTPA = 50 nm) from the yellow emission of 2.322 eV (534 nm) to the red emission of 2.123 eV (584 nm), showing an obvious MFC phenomenon (Fig.…”
Section: Mfc Behaviorsmentioning
confidence: 99%
“…It has been reported that the cyanostyrene derivatives could exhibit MFC properties and the planar architecture of pyrenebased conjugated compounds is favorable for MFC. 38,[40][41][42] To test their possible MFC properties, the solid-state fluorescence changes of PYTPA and PYPHTPA were examined before and after grinding. The emission peak of PYTPA exhibits a red shift of 0.199 eV (Δλ PYTPA = 50 nm) from the yellow emission of 2.322 eV (534 nm) to the red emission of 2.123 eV (584 nm), showing an obvious MFC phenomenon (Fig.…”
Section: Mfc Behaviorsmentioning
confidence: 99%
“…The sulfur atom of phenothiazine is in the +2-oxidation state (sulfide form) and can be oxidized to the +6-oxidation state (sulfone) which substantially changes its electronic properties . The electron-rich S-atom in the sulfide state makes the phenothiazine molecule a strong electron donor, whereas the electron-deficient S-atom in the sulfones causes phenothiazine to act as an electron acceptor. , A variety of phenothiazine compounds have been effectively used in mechanochromic applications in the literature. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, photochromic and mechanochromic materials are considered to be the most promising anti-counterfeiting materials due to their advantages of easy operation and eco-friendliness. [20][21][22][23][24][25][26][27] Spiropyran (SP) as a typical photochromic and mechanochromic molecule with a unique photoinduced fluorochromic property has drawn great attention. Under ultraviolet light radiation, spiropyran can convert to an open-ring state (MC).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, photochromic and mechanochromic materials are considered to be the most promising anti-counterfeiting materials due to their advantages of easy operation and eco-friendliness. 20–27…”
Section: Introductionmentioning
confidence: 99%